Outcome of Long Saphenous Vein Stripping and Multiple Phlebectomy for Treatment of Varicose Vein and Venous Ulcer - Islam, Sardar Rezaul; Sarkar, Shah Alam; Paul, Debabrata; Poran, Shah; Golap, Haldar Kumar; Rahman, Mushfiqur; Chowdhury, Adiba; Sarkar, Bithika; Akmol, Ivy (British Journal of Healthcare and Medical Research, 2026)
Background: Long saphenous vein stripping and multiple phlebectomy in leg is a classical surgical procedure for varicose vein. This operation consists sapheno-femoral junction ligation, long saphenous vein stripping and multiple ligation-avulsion of leg varicose veins. Endo-venous laser ablation, endo-venous radiofrequency ablation and sclerotherapy are minimal invasive technique for varicose vain. Many studies have shown that open surgery is still superior to minimal invasive techniques as postoperative recurrence is concerned. Minimal invasive technique is not available in many centers. It is expensive also. We presented outcome of this classical surgery for chronic venous insufficiency in lower limb and venous ulcer. Materials and method: We operated 59 limbs with varicose veins from 2015 to 2025 for a period of 10 years. We operated 48 patients with 59 lowers limbs. Seven of them presented with venous ulcer. All were evaluated by duplex imaging before surgery. Stripping of long saphenous vein and multiple ligation-avulsion of leg varicosities were done for all patient. Eleven of them had excision of short saphenous vein for short saphenous incompetence. They were followed for a period of one year. Results: 56 limbs had complete recovery from varicose vein. Venous ulcers have completely within 8 weeks. Two limbs developed deep vein thrombosis and was treated by Warferine. There were a single recurrence in one limb. Conclusion: Classical long saphenous vein stripping with multiple phlebectomy in leg has excellent outcome even in presence of venous ulcer. It has minimum recurrence. It is cheap compared to endo-venous procedure. Despite slightly more postoperative complication it is still gold standard treatment of varicose vein and its complication.